2020
DOI: 10.1029/2020wr027989
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Volumetric Water Storage in Monsoonal Wetlands of Northeastern Bangladesh

Abstract: The volume of water stored in seasonal wetlands is a fundamental but difficult to measure variable for developing a physical understanding of wetland behavior. For seasonal wetlands that are a major source of water for rice and fish production, this physical understanding is key to planning for water-food security and ecosystem services. This study quantified variations in volumetric storage for the numerous seasonal wetlands of northeastern Bangladesh, locally known as "haors." These haors receive transbounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…Incidence angle also plays an important role in the image pre-processing; for the water surface classification, and we considered look angles from 31.7⁰ to 45.4⁰. More details on this choice are described by Ahmad et al [29]. With the pre-processed image, a backscatter threshold of -13db was selected to identify the water body, as suggested by Liu [45].…”
Section: ) Sentinelmentioning
confidence: 99%
See 3 more Smart Citations
“…Incidence angle also plays an important role in the image pre-processing; for the water surface classification, and we considered look angles from 31.7⁰ to 45.4⁰. More details on this choice are described by Ahmad et al [29]. With the pre-processed image, a backscatter threshold of -13db was selected to identify the water body, as suggested by Liu [45].…”
Section: ) Sentinelmentioning
confidence: 99%
“…To estimate the volume variation, we linearly interpolated the water surface area data, so that the timestamps of both water elevation and interpolated water surface area were the same, which makes it easier to calculate the volume change. The information of the exact bathymetry of the water bodies was not available, so we estimated the volume stored with respect to the lowest observed water surface elevation in the time series, similar to Ahmad et al [29] who had earlier applied citizen scientist height data for northeastern wetlands of Bangladesh. The lowest water elevation observation was obtained from the LOCSS website over the period of the study.…”
Section: B Extracting Water Surface Elevationmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have been reported in recent years, in which different methodologies have been used for the volumetric study of water storage in wetlands. One of the reported procedures has been the combination of SAR imagery, which provides continuous surface data without cloud interference [40], with elevation data provided by altimetric radars such us ENVISAT RA-2 GDR, PALSAR-2, Jason-3 and Sentinel-3, among others [34,[41][42][43]. These studies were able to estimate variations in the volumetric storage of wetlands of different hydrological characteristics.…”
Section: Introductionmentioning
confidence: 99%